Les aspects évolutifs des exposants de la réciprocité médiévaux. Anciennes et nouvelles méthodes de recherche - Nkollo, Mikołaj (Studia Romanica Posnaniensia, 2012)
The present paper revolves around unusual paths of grammaticalization of Old French (12th century) reciprocal markers. This methodological framework requires medieval means of expressing reciprocity to be compared both with their parent forms in Classical Latin and with the markers introduced in subsequent stages of the history of French language. The first hypothesis deals with how parallel markers, i.e. ones that have a common origin and that are used inside the same area of grammar (se… entre- and entre eux < Lat. inter se), are different from each other. This path is claimed to materialize provided one of the two terms begins to serve a particular function not performed by the other one. The second hypothesis accounts for what means were used to prevent ongoing reflexive / reciprocal homonymy. This task happened to be provisionally fulfilled by cors a cors and coste a coste until the advent of adverbs ending in -ment in 14th century. As a consequence, body-part nouns lost most of their grammatical potential. The third hypothesis, formulated in terms of exaptation, explains how and why languages are likely to recycle erstwhile peripheral lexical elements. This evolutionary path takes place in response to a need to convey a given meaning unambiguously. Attempts at avoiding reflexive / reciprocal homonymy prompted the revival of seemingly forgotten Latin items reciprocus / mutuus. Concluding remarks address the problem of whether the concept of exaptation is useful in historical linguistics and contain a proposal towards constraining its scope. As for current views of grammaticalization, this notion seems to call for further refinements, as well.